College students’ learning perceptions and outcomes in different classroom environments: A community of inquiry perspective - Hu, Yan; Huang, Jinyan; Kong, Fanzhe (Frontiers in Psychology, 2022)
This study examined the significant differences in Chinese college students’ learning perceptions and outcomes between the “quasi smart” and smart classrooms under the perspective of the community of inquiry (CoI) framework. The participants were 275 freshmen students who took the “college physics” hybrid course in the spring of 2022 at a four-year university in central China. Data were collected from the CoI survey, a follow-up focus group interview with ten randomly selected student participants, and a semi-structured interview with the instructor. The results indicated that the students’ perceptions of the teaching, social, and cognitive presences were significantly higher in the smart classroom than in the “quasi smart” classroom; further, students in the smart classroom achieved significantly higher course marks than those in the “quasi smart” classroom. The pros and cons of these two different classroom environments were identified by the participating students and their course instructor.